How Lecturers, Supervisors, and MGMP PAI Collaborate in Sustainable Professional Development (PKB): an Observation in Sleman Regency - Sabarudin Sabarudin; Muhammad Nurul Mubin; Zaenal Arifin; Wahidatun Maulida; Ahmad Maulana Asror (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This research aims to illustrate the collaboration of lecturers, students, supervisors, and MGMP in the development of sustainable professional teachers in Sleman Regency. This research uses a qualitative approach with descriptive research types of cooperation among lecturers, students, supervisors, and MGMP in the development of sustainable professional pai teachers in Sleman Regency. Data collection is done through telephone interviews and/or cloud meeting zooms. As well as spreading the questionnaire, it was done using a Google form given to MGMP members through WhatsApp messages. The results showed the importance of collaborating with teachers and supervisors who feel the need for help and competent speakers and lecturers who have funds and expertise for service and develop the quality of education in the local region of their universities. The form of collaboration is the training of PTK, LKPD, and Canva Learning Media Development. The busy schedules of many MP members, limited funds, and poor communication between supervisors, MGMP, and universities are all barriers to collaboration. The supporting factors are the existence of new regulations that encourage the development of kopetensi, the creativity of MGMP supervisors in establishing communication with universities, the allocation of funding from universities, and alumni networks as information distributors or liaisons. This research is expected to provide an overview and a theory about the form of cooperation between lecturers, students, supervisors, and MGMP.